TIdentity module for the reconstruction of the moments of multiplicity distributions - Arslandok, Mesut; Rustamov, Anar (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
In this report a new software module for the reconstruction of the moments of multiplicity distributions of identified particles, the TIdentity module, is presented. The module exploits the Identity Method, which allows to circumvent the issues of incomplete particle identifications caused by unavoidable overlapping particle identification signals. After demonstrating the performance of the module in a number of simulations, we provide a user’s guide with a detailed description of its functionality. The module can be used in high energy nuclear interactions aiming at the determination of the moments of multiplicity distributions of identified particles.